0144 Assessing and addressing non-response at follow-up in the gulf study. (21st August 2017) - Strelitz, Jean; Keil, Alex; Richardson, David; Gammon, Marilie; Kwok, Richard; Sandler, Dale; Engel, Lawrence
Abstract : Background: The Gulf Long Term Follow-up (GuLF) STUDY is the first investigation to assess coronary heart disease (CHD) among oil spill workers. Participant non-response to periodic follow-up interviews can impact the ability to measure CHD over time. Describing predictors of non-response and the impact on analyses will improve generalizability of results to the study population. Objective: Assess predictors of non-response at the first follow-up interview in the GuLF STUDY and use inverse probability (IP) weights to account for these in an analysis of oil spill cleanup work duration and CHD. Methods: We examined covariate distributions between those who did (n=21, 245) and did not (n=10, 364) complete the follow-up interview, and constructed IP censoring weights to account for these differences. We applied the weights to estimate cohort-level hazard ratios (HR) and 95% confidence intervals (95% CI) for oil spill cleanup work duration and self-reported nonfatal CHD. Results: Those who participated in the follow-up interview were more likely to be older, have higher income and education, and were less likely to be smokers. After applying IP censoring weights and controlling for confounding, work duration (>180 days vs. 1–30 days) was non-significantly associated with nonfatal CHD [HR (95% CI)=1.50 (0.92–2.43)]. The results were similar without censoring weights [HR (95% CI)=1.41 (0.87–2.27)]. Conclusions: Several factors were associated with participation in the GuLF STUDY follow-up interview, however results for work duration and CHD were robust to censoring. Weighting improved generalizability of results but did not change conclusions about the association between work duration and CHD.